Exploring the effect of psychological capital on teachers’ organizational commitment through interpersonal communication - Irvandi Gustari; Widodo Widodo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study explores the effect of psychological capital (PsyCap) on teachers' organizational commitment, mediated by interpersonal communication. The research data was collected by the questionnaire: PsyCap, interpersonal communication, and organizational commitment in a Likert scale model through the survey methods toward 303 teachers of State Junior High School in Indonesia. Data analysis uses path analysis supported by descriptive statistics and correlational. The results show that PsyCap affects teachers' organizational commitment through interpersonal communication. Thus, the teachers' organizational commitment can improve through PsyCap and interpersonal communication. This finding can be discussed as a reference among researchers and practitioners to develop better models of teachers' organizational commitment in various contexts in the future.